Щодо аналізу методів редизайну сайтів та мобільних додатків - Заратуйко, М. О. (ХНУРЕ, 2023)
This paper is dedicated to analysis of different redesign methods, their advantages and disadvantages. Such methods as conversions increasing, user experience improving and increasing of user loyalty were identified as the most suitable for achieving an established goal. In addition, it is important to learn what tools and techniques can be used in redesign to achieve the desired result, and what aspects need to be considered when developing a redesign strategy.
Keywords: редизайн сайту; redesign method